(untitled) (Research, Society and Development, 2022)
Studies report a close relationship between the increase of anxiety and depression disorders in the young population and academic routine, especially when considering the medical course. At the same time, due to the easy access and the popular belief of harmlessness, nervous system acting herbal medicines are being much sought after by this group. Thus, this research aimed to trace the consumption profile of central nervous system acting natural products in medical students at a public university in northeastern Brazil. To this end, information was collected through an online form containing specific direct questions to medical students from a public university in northeastern, considering the inclusion and exclusion factors. It was registered on the Brazil Platform of the Ministry of Health. – CAAE No. 50027121.0.0000.5011. The study had 125 participants, where 59 participants claimed to use or have used nervous system acting herbal medicines, with Passiflora incarnata and Valeriana officinalis being the most used species. Inadequate practices were found, such as self-medication and prescription change. College related issues proved to be important psychosocial stressors and incentives for the use of natural psychotropic drugs. Finally, the research presented similarities with the literature, evidencing a wide use, without proper professional advice, of herbal medicines among medical students.